2014
DOI: 10.1088/0953-2048/27/10/104006
|View full text |Cite
|
Sign up to set email alerts
|

Doping-evolution of the superconducting gap in single crystals of (Ca1−xLax)10(Pt3As8)(Fe2As2)5superconductor from London penetration depth measurements

Abstract: The doping-evolution of the superconducting gap structure in iron-based superconductor (Ca −x min c ). Both the decrease of the exponent and the increase of the absolute value of Δλ in the underdoped regime are similar to the observations in other charge-doped iron-based superconductors, such as doped BaFe 2 As 2 and NaFeAs, suggesting a universal behavior in iron-based superconductors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…And recent angle resolved photoemission spectroscopy (ARPES) experiment further suggested that this difference between two compounds could be developed by the number of the band-edge singularities 9 . In order to study this subtle relation between the electronic structure and superconductivity in these materials, various experiments have already been performed: such as transport 10 , pressure effect 11 , ARPES 7 , magnetic force microscope (MFM) 12 , upper critical field (H c2 ) 13 , nuclear magnetic resonance (NMR) 14 , and penetration depth λ(T ) 15 measurements, etc. However, the IR spectroscopy experiment has not yet been carried out with these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…And recent angle resolved photoemission spectroscopy (ARPES) experiment further suggested that this difference between two compounds could be developed by the number of the band-edge singularities 9 . In order to study this subtle relation between the electronic structure and superconductivity in these materials, various experiments have already been performed: such as transport 10 , pressure effect 11 , ARPES 7 , magnetic force microscope (MFM) 12 , upper critical field (H c2 ) 13 , nuclear magnetic resonance (NMR) 14 , and penetration depth λ(T ) 15 measurements, etc. However, the IR spectroscopy experiment has not yet been carried out with these compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The uncertainty of the λ extrapolation from 4 K to 0 K is as small as few percent, and thus negligible compared to the main source of the uncertainty. 11 The 10-4-8 phase Ca 10 (Pt 4−δ As 8 )[(Fe 0.97 Pt 0.03 ) 2 As 2 ] 5 with δ ≈ 0.246 and T c = 26.5 K shows H c2 (0) values of around 90 T for H//c and 92 T for H//ab. 14 The upper critical field anisotropy thus changes from ≈ 7 close to T c to ≈ 1 at low temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Superconductivity in this system occurs under applied pressure 8 or with chemical doping. [9][10][11] The two different types of intermediate layers (n = 3 and n = 4) affect significantly the physical properties of these highly anisotropic compounds. 5,12 For example, the optimally doped Ca 10 (Pt 3 As 8 )[(Fe 1−x Pt x ) 2 As 2 ] 5 has a superconducting transition temperature (T c ) around 10 K and an upper critical field of H c c2 (0) ∼ 20 T. 13 The upper critical field anisotropy (γ = H ab c2 /H c c2 ) decreases from 10 close to T c to 1.5 at low temperatures.…”
mentioning
confidence: 99%
“…And recent angle resolved photoemission spectroscopy (ARPES) experiment further suggested that this difference between two compounds could be developed by the number of the band-edge singularities 9 . In order to study this subtle re-lation between the electronic structure and superconductivity in these materials, various experiments have already been performed: such as transport 10 , pressure effect 11 , ARPES 7 , magnetic force microscope (MFM) 12 , upper critical field (H c2 ) 13 , nuclear magnetic resonance (NMR) 14 , and penetration depth λ(T ) 15 measurements, etc. However, the IR spectroscopy experiment has not yet been carried out with these compounds.…”
Section: Recently Discoveredmentioning
confidence: 99%